1987
DOI: 10.1002/pen.760272205
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a separator in a sheet die on the anisotropy of tear strength of extruded medium density polyethylene

Abstract: Sheets of medium density polyethylene (MDPE) were extruded through a slit die containing an internal separator. Thus, the melt stream was momentarily split before emerging from the die. A line of separation was evident in the extruded sheets. It is attributed to incomplete welding or healing. Measurements of tear energy G, revealed that the extruded sheets were anisotropic and that the weld line was extremely weak after extrusion start-up, only about V5 of the strength elsewhere. As extrusion continued, the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…For ABS a straightforward correlation of molecular orientation, which was measured by using thermal conductivity and thermally induced shrinkage, with critical strain was observed. Gent, et aL (4), have found the extrusion temperature dependence of the anisotropy in an extruded medium density PE by measuring the tear energy. They found that when the die temperature of the extruder is 150°C.…”
mentioning
confidence: 99%
“…For ABS a straightforward correlation of molecular orientation, which was measured by using thermal conductivity and thermally induced shrinkage, with critical strain was observed. Gent, et aL (4), have found the extrusion temperature dependence of the anisotropy in an extruded medium density PE by measuring the tear energy. They found that when the die temperature of the extruder is 150°C.…”
mentioning
confidence: 99%
“…Ludwig et al discovered that polyethylene (PE) with a broad molecular weight distribution has superior long-term mechanical properties [ 13 ]. Meanwhile, many researches have proven that the formation of a shish-kebab structure and more perfect crystals can help to enhance the resistance of polymer to SCG to a large extent [ 11 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%